Robust switched control design for electrically stimulated lower limbs: A linear model analysis in healthy and spinal cord injured subjects - Teodoro, Ricardo G. [UNESP] (2020)
Functional electrical stimulation (FES) has been used to restore and aid motor functions in paraplegics, promoting better therapeutic results for its users. From experimental results, one can observe that there exists an uncertain term added to the control signal for a given operating point, because of the plant uncertainties. An experimental setup is presented to identify a linear model containing uncertainties. Then, robust single-gain controllers and suitable switched controllers are designed for compensating the uncertain term added to the control signal. Open-loop technique, robust single-gain and robust switched controllers are numerically compared. The experimental results show the regulation for five healthy and four paraplegic individuals. The successful run time when the robust switched control is used along with a smooth switching signal is higher than those of other studies presented in the literature. In addition, the results indicate that compared with the robust single-gain controller, the robust switched controller minimizes the influence of the parametric uncertainties, returns the smallest time-derivative value of the Lyapunov function, and presents higher feasibility and lower gain norm to control the system.